2004
DOI: 10.1002/fut.10114
|View full text |Cite
|
Sign up to set email alerts
|

Switching asymmetric GARCH and options on a volatility index

Abstract: Few proposed types of derivative securities have attracted as much attention and interest as option contracts on volatility. Grunbichler and Longstaff (1996) is the only study that proposes a model to value options written on a volatility index. Their model, which is based on modeling volatility as a GARCH process, does not take into account the switching regime and asymmetry properties of volatility. We show that the Grunbichler and Longstaff (1996) model underprices a three-month option by about 10%. A Switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Hence, the previously reported results are robust to the choice of a zero value for the volatility risk premium. This is in line with the results in Daouk and Guo (2004) who also found that the effect of model error on the pricing performance of the GL model is not affected by the choice of the volatility risk premium.…”
Section: The Effect Of a Non-zero Volatility Risk Premiumsupporting
confidence: 91%
See 3 more Smart Citations
“…Hence, the previously reported results are robust to the choice of a zero value for the volatility risk premium. This is in line with the results in Daouk and Guo (2004) who also found that the effect of model error on the pricing performance of the GL model is not affected by the choice of the volatility risk premium.…”
Section: The Effect Of a Non-zero Volatility Risk Premiumsupporting
confidence: 91%
“…For example, Brenner et al (2001) suggest the introduction of options on straddles. Finally, it may be worth studying the hedging effectiveness of volatility options and the impact of model error for alternative data generating processes (see e.g., Wu 2002, andDaouk andGuo 2004). In the interests of brevity, these extensions are best left for future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These were based on a discrete-time GARCH volatility process and its continuous time counterpart developed by Heston and Nandi (2000b). Recently, Daouk and Guo (2004), studied the valuation of volatility options based on a Switching Regime Asymmetric GARCH process for the underlying.…”
Section: Introductionmentioning
confidence: 99%